(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aimed to define performance auditing and the INTOSAI standards and guidelines issued regarding performance auditing, and to explain the concept of the conceptual framework and application procedures and the nature of specialized funds (FUND) and the literature on performance auditing, in addition to presenting a proposed audit program to audit the Reconstruction Fund for Affected Areas according to the INTOSAI Standard (3000) and the standards and guidelines referred to in this standard. The analytical approach was used in this research, and the researchers used a set of tools to achieve the research objectives, which were represented by collecting and analyzing data, and analyzing the financial statements of the Reconstruction Fund for Areas Affected by War Operations in order to understand the nature of the Fund’s activity, in addition to examining and analyzing the documentary collection, documents and data, and preparing a proposed audit program according to the INTOSAI standards and guidelines and relevant international standards. The research sample was represented by the Reconstruction Fund for Areas Affected by War Operations for the years (2015-2020), since most of the Fund’s programs and projects were in this period. The research reached a set of conclusions, the most important of which are: understanding the nature of the Fund’s activity, its organizational structure and tasks The powers of its departments help guide the auditor towards formulating performance audit procedures that help verify the efficiency, effectiveness and economy of the fund. The researchers recommended that the supervisory bodies concerned with auditing the Reconstruction Fund for Areas Affected by War Operations should pay attention to implementing the performance audit process on the fund at close intervals or forming a special committee to complete this process due to the importance of the fund and the large allocations allocated to it.